The Problems of the Relationship between Science and Religion in Qibla Direction Calibration at the Great Mosque of Demak and Baiturrahman Mosque in Semarang, Indonesia - Izzuddin, Ahmad (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
The relationship between science and religion in the practice of Islamic law (fiqh) is dilemmatic. On the one hand, science is in harmony with religion, and the two are mutually exclusive on the other hand. This article includes the last category by presenting evidence from two cases of Qibla direction calibration in Indonesia. The author focuses on the disagreement between fiqh and scientific results on the calibration of the Qibla direction at the Great Mosque of Demak and Baiturrahman Mosque in Semarang, Indonesia. Using literature research and content analysis, the author finds that fiqh’s rejection of science lies in the intersection of fiqh with Sufistic elements and the reality of social establishment. In the Qibla’s case direction at the Great Mosque of Demak, they believe that Sunan Kalijaga determined the direction of the Qibla in the mosque, and the mosque has a switched historic value. In contrast to the case of the Qibla direction at the Baiturahman Mosque in Semarang, which has no historical value and the Qibla direction was previously determined using a simple tool, they reasoned that changing the prayer lines in the mosque could cause discomfort and lack of stability for the congregation when carrying out prayer rituals. Thus, a scientific integration approach is needed in handling the gap between science and religion in religious practice in Indonesia.